The development strategy of innovation in universities - Шеденов, У.; Нуртазин A.; Сулейменов, И. (Journal of Economic Research & Business Administration, 2017)
The paper considers the policy of innovation in the universities (as a complex system) which is considered on the principle of unity of learning and scientific research that must be supplemented by the need of participation in innovation activity with creation of economic stimulating tools to ensure and prioritize the motivation to participate in innovation activities, and to obtain sufficient skill level that meets the needs of the establishment of the knowledge-based economy. Moreover ensuring the commercialization of scientific, practical and technical work is the cornerstone moment in the development of a new type of economy. This economic policy will lead to a revision of training programs for Bachelors and Masters followed by the inclusion elective disciplines to ensure the development of skills and competencies of the students, and allow them to be directly involved in innovation activities. The innovation development strategy of universities will be the basis of this economic policy of the universities.